2017
DOI: 10.5194/nhess-17-749-2017
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous winter-snow-amplified earthquake-induced disaster of the 2015 Langtang avalanche in Nepal

Abstract: Abstract. Coseismic avalanches and rockfalls, as well as their simultaneous air blast and muddy flow, which were induced by the 2015 Gorkha earthquake in Nepal, destroyed the village of Langtang. In order to reveal volume and structure of the deposit covering the village, as well as sequence of the multiple events, we conducted an intensive in situ observation in October 2015. Multitemporal digital elevation models created from photographs taken by helicopter and unmanned aerial vehicles reveal that the deposi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 19 publications
(29 reference statements)
1
44
1
Order By: Relevance
“…Previous studies have shown the good performance of adding a conceptual representation of the storage and drainage in the glaciers within glaciohydrological models (e.g., Jansson et al, 2003;Hock and Jansson, 2006). The most widely adopted approach is based on a reservoir or a cascade of reservoirs with time-invariant parameters (e.g., Farinotti et al, 2012;Zhang et al, 2015;Hanzer et al, 2016;Gao et al, 2017). Here, storage of liquid water inside glaciers was implemented by adding an englacial porous layer between the glacier and the bedrock allowing the liquid water storage within the glacier.…”
Section: Glacier Parameterizationmentioning
confidence: 99%
“…Previous studies have shown the good performance of adding a conceptual representation of the storage and drainage in the glaciers within glaciohydrological models (e.g., Jansson et al, 2003;Hock and Jansson, 2006). The most widely adopted approach is based on a reservoir or a cascade of reservoirs with time-invariant parameters (e.g., Farinotti et al, 2012;Zhang et al, 2015;Hanzer et al, 2016;Gao et al, 2017). Here, storage of liquid water inside glaciers was implemented by adding an englacial porous layer between the glacier and the bedrock allowing the liquid water storage within the glacier.…”
Section: Glacier Parameterizationmentioning
confidence: 99%
“…Cyclone Hudhud in October 2015 caused a disaster that killed more than 50 people within 2 days in the Annapurna and Manaslu regions in Nepal as a result of sudden snowfall and avalanches (Sherpa et al 2017). Anomalous winter snow accumulation also amplified the earthquake-induced disaster that killed more than 350 people and destroyed the entire village of Langtang in Nepal in 2015 (Fujita et al 2017).…”
Section: Disservices: Cryosphere-related Disastersmentioning
confidence: 99%
“…This event consisted of multiple phenomena and was described as a "disaster within a disaster" (Kargel et al, 2015). The sediment deposition consists mostly of accumulated snow and, to a lesser extent, of glacier ice (Fujita et al, 2017). Satellite-based thermal infrared observation conducted 5 days after the quake revealed that the deposition had a 10-20 K lower surface temperature than the surrounding terrain (Kargel et al, 2015).…”
Section: Avalanche Eventmentioning
confidence: 99%
“…The water stream of the Langtang river was blocked once by the deposition but quickly recovered as the ice and snow deposition melted (Kargel et al, 2015). The materials near the riverbed had less boulder-and sand-rich deposition, suggesting that they originated from a snow avalanche (Fujita et al, 2017). From the sediment volume and catchment area on the mountain hill, the original snow depth before the avalanche occurrence was estimated at 1.82 m in the catchment hillslopes (Fujita et al, 2017).…”
Section: Avalanche Eventmentioning
confidence: 99%
See 1 more Smart Citation